2018
DOI: 10.1101/497628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of a novel mutation G511T in the 530 loop in 16S rRNA in multi drugs resistant Mycobacterium tuberculosis isolated from Sudanese patients

Abstract: Background: Tuberculosis (TB) is a bacterial disease considered as a global public health emergency by the World Health Organization (WHO) since 1993. In Sudan, MDR-TB represents a growing threat and one of the most important challenges that faced national tuberculosis program to establish a comprehensive multidrug-resistant tuberculosis management system.Objective: To characterize the diversity and frequency of mutations in Sudanese MDR-TB strains isolated from Wad Madani, Al-Gadarif and Khartoum using 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The PCR reaction mixtures contained 2.5U of i-Taq TM DNA polymerase (5U/µl), 2.5mM of each deoxynucleoside tri-phosphates (dNTPs), 1X of PCR reaction buffer (10X),1X of gel loading buffer and 1µl of DNA template. The temperature cycle for the PCR was carried out using a method described previously (41,42). To detect the DNA, 3µl of each PCR products was loaded onto 2% agarose gels stained with 3µl ethidium bromide (10mg/ml) and subjected to electrophoresis in 1x Tris EDTA Buffer (TEB buffer) (89mM of Tris base, 89mM Boric acid and 2mM EDTA dissolved in 1Litter H 2 O) for 30 min at 120V and 50mA.…”
mentioning
confidence: 99%
“…The PCR reaction mixtures contained 2.5U of i-Taq TM DNA polymerase (5U/µl), 2.5mM of each deoxynucleoside tri-phosphates (dNTPs), 1X of PCR reaction buffer (10X),1X of gel loading buffer and 1µl of DNA template. The temperature cycle for the PCR was carried out using a method described previously (41,42). To detect the DNA, 3µl of each PCR products was loaded onto 2% agarose gels stained with 3µl ethidium bromide (10mg/ml) and subjected to electrophoresis in 1x Tris EDTA Buffer (TEB buffer) (89mM of Tris base, 89mM Boric acid and 2mM EDTA dissolved in 1Litter H 2 O) for 30 min at 120V and 50mA.…”
mentioning
confidence: 99%
“…This mixture was added to the PCR master mix (GoTaq, Promega, USA) following the manufacturing guide. Then, run with a thermal cycler (SensoQuest, Germany) as follows: 30 cycles were performed in a thermocycler, each cycle has three steps of denaturation (95 °C for 1 min), annealing (54 °C for 1 min), extension (72° C for 3 min) and final extension time of 72 °C for 5 min [ 8 ]. Amplified products were analyzed by conventional electrophoresis, Bands were determined using an Imagemaster VDS image analysis system (SCIE-PIAS VISION U.K) [ 17 ].…”
Section: Main Textmentioning
confidence: 99%
“…Few studies have been published in Sudan on 16S rRNA gene sequencing. As described by Hassan et al [ 8 ], who showed the significance of microbial identification and phylogenetic markers for Staphylococci species from Sudanese isolates used for taxonomy. Prior research also been explored in Sudan by Merghani et al, suggested that PCR assay with primers targeted to the 16S rRNA gene sequence offered a useful method for the identification of bacteria to the species level and differentiated one species from others [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mixture was added to the PCR master mix (GoTaq, Promega, USA) following the manufacturing guide. Then, run with a thermal cycler (SensoQuest, Germany) as follows: 30 cycles were performed in a thermocycler, each cycle has three steps of denaturation (95°C for 1 min), annealing (54°C for 1 min), extension (72° C for 3 min) and nal extension time of 72°C for 5 min [7]. Ampli ed products were analyzed by conventional electrophoresis, Bands were determined using an Imagemaster VDS image analysis system (SCIE-PIAS VISION U.K) [15].…”
Section: Pcr Ampli Cation Of 16s Rrna Genementioning
confidence: 99%
“…Few studies have been published in Sudan on 16S rRNA gene sequencing. As described by Hassan et al, who showed the signi cance of microbial identi cation and phylogenetic markers for Staphylococci species from Sudanese isolates used for taxonomy [7]. Prior research also been explored in Sudan by Merghani et al, suggests that PCR assay with primers targeted to the 16S rRNA gene sequence offered a useful method for the identi cation of bacteria to the species level and differentiated one species from others [8,9].…”
Section: Introductionmentioning
confidence: 99%